• Vypočítaj:3 3/5 : (0,4 : 3/7) =
  • Vypočítaj: 2 1/12 . 8/15 – 5/3 . (1/2 + 1/6) =
  • Vypočítaj: 2,4 . ¾ - 1/5 . (1 + ½) =
  • Vypočítaj: (2 + 5/6 – 2/3) / (2 1/6 – 3 – ¼) =
  • Vypočítaj: [6 3/10 : (1 3/5 + ½)] – 1/3 =
  • Vypočítaj {[(-1/3) + 1/6] : (-3/5)} / (4/9 + 0,9 . 2/3) =
  • Vypočítaj: 1 ½ - 2 ¾ : [ -2/3 + (-0,2 – 4/5) . 1/2] =
  • Vypočítaj: {[(-1/3 + 1/6) : (-3/5)] / (4/9 + 0,9 . 2/3)} . 47/25 =
  • Vypočítaj:[2 1/3 – 3 . (4 – 8/3)] : [1 – (2/3 – ¼)] =
  • Vypočítaj: 2 – 1/7 . (2 ½ - 2/3) + 2 . (-1/3) =